Delineation of a novel neurodevelopmental syndrome associated with PAX5 haploinsufficiency. Issue 4 (30th January 2022) - Gofin, Yoel; Wang, Tianyun; Gillentine, Madelyn A.; Scott, Tiana M.; Berry, Aliska M.; Azamian, Mahshid S.; Genetti, Casie; Agrawal, Pankaj B.; Picker, Jonathan; Wojcik, Monica H.; Delgado, Mauricio R.; Lynch, Sally A.; et al.
Abstract: PAX5 is a transcription factor associated with abnormal posterior midbrain and cerebellum development in mice. PAX5 is highly loss‐of‐function intolerant and missense constrained, and has been identified as a candidate gene for autism spectrum disorder (ASD). We describe 16 individuals from 12 families who carry deletions involving PAX5 and surrounding genes, de novo frameshift variants that are likely to trigger nonsense‐mediated mRNA decay, a rare stop‐gain variant, or missense variants that affect conserved amino acid residues. Four of these individuals were published previously but without detailed clinical descriptions. All these individuals have been diagnosed with one or more neurodevelopmental phenotypes including delayed developmental milestones (DD), intellectual disability (ID), and/or ASD. Seizures were documented in four individuals. No recurrent patterns of brain magnetic resonance imaging (MRI) findings, structural birth defects, or dysmorphic features were observed. Our findings suggest that PAX5 haploinsufficiency causes a neurodevelopmental disorder whose cardinal features include DD, variable ID, and/or ASD.